Classic Ronchi test and its variants for quality control of various optical surfaces - Malenko, A.S.; Borovytsky, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Performed in this work is the analysis of the optical Ronchi interferometer circuit and its upgrading to test quality of various optical surfaces. Briefly described in this paper is the classic test by Ronchi, shown is every upgraded circuit diagram of the interferometer and their principle of operation. Also, it is demonstrated interferential patterns for each method allowing one to determine which aberrations are present in the tested optics. With this method, when one can only visually detect aberrations, it seems to be not accurate. But with digital image processing the interferential pattern, special mathematical models and algorithms, aberrations that are present in the optical surface can be calculated with very high accuracy. Therefore, the methods of control offered in this paper provide fast and accurate results for the data circuits to be simply assembled and configured.